2019
DOI: 10.36263/nijest.2019.02.0154
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrates’ Pollution Tolerance Index in Calabar River, Cross River State, Nigeria

Abstract: A study was undertaken to determine the macroinvertebrates pollution tolerance index (PTI) in Calabar River, Cross River state, Nigeria. Five sampling stations were chosen along the river course: Ikot Okon Abasi, Tinapa, Unicem, Marina resort and Nsidung beach which were labeled stations 1, 2, 3, 4 and 5 respectively. Physico-chemical parameters; surface water temperature, pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), total dissolved solids (TDS) and total suspended solids (TSS) were measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Each gold mining site was divided into quadrants where sample locations were carefully chosen based on the size of the site after a pre–sampling survey, sampling spots were cleaned of debris while composite topsoil with depth from 0 to 15 centimeters were collected from different selected locations using soil auger so as to provide representative coverage of each mining site and the control area according to [ 27 , 28 ]. There were 12 sampling spots in Kwali, 8 in Maraba, 7 in Duke and 8 in Kadauri from where the collected soil samples were homogenized and transferred into clean polythene bags which were immediately transported to the laboratory for heavy metals analyses, this was done monthly for a period of 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Each gold mining site was divided into quadrants where sample locations were carefully chosen based on the size of the site after a pre–sampling survey, sampling spots were cleaned of debris while composite topsoil with depth from 0 to 15 centimeters were collected from different selected locations using soil auger so as to provide representative coverage of each mining site and the control area according to [ 27 , 28 ]. There were 12 sampling spots in Kwali, 8 in Maraba, 7 in Duke and 8 in Kadauri from where the collected soil samples were homogenized and transferred into clean polythene bags which were immediately transported to the laboratory for heavy metals analyses, this was done monthly for a period of 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported signs of pollution from untreated industrial effluents, municipal wastewater, run-off from agricultural chemical fertilizers and pesticides, as well as spillage of petroleum products in Calabar River [9] hence this study was conducted to assess the levels of heavy metals and total petroleum hydrocarbon (TPH) in water and tissues of periwinkles (Tympanotonus fuscatus L.) obtained from the River in order to determine their suitability for human consumption.…”
Section: Introductionmentioning
confidence: 99%